Community‐level spatial structure supports a model of stochastic geometry in species‐rich shrublands. Issue 6 (9th December 2016) - Perry, George L. W.; Miller, Ben P.; Lamont, Byron B.; Enright, Neal J.
Abstract : In some ecosystems a small suite of species can determine community‐level patterns of species richness by acting as either 'accumulators' or 'repellers'; that is, the richness of the immediate neighbourhood of such species departs from that expected on the basis of a given null model. Using the individual species‐area approach, we evaluated community‐level spatial pattern in four species‐rich shrublands (two 40 × 40 m and two 30 × 30 m plots) by assessing the frequency of accumulator and repeller species and whether any such species were associated with specific life‐history characteristics. Few species departed from the expectations of the null spatial model that we used, although, at three of the four sites, accumulators were more common than repellers. Departures from the null model we assessed were most prevalent within just 1 m of focal individuals and were not consistently associated with specific life‐history traits. Model‐based clustering suggests that there are distinct sub‐communities in each of the four communities, but while internally spatially cohesive, these sub‐communities intermingle and their membership is not predictable from the life‐history traits of their constituent species. Comparable analyses in other species‐rich systems have also detected a similar absence of spatial interactions. The disturbance regime in the shrubland communities we consider is markedly different from those in the forest ecosystems where previous studies have been concentrated (recurrent fire versus infrequent gap‐phase dynamics) and resources are more limiting. Thus, our results provide further support for the generality of a model of stochastic geometry, likely underpinned by stochastic dilution effects, in species‐rich plant communities.